Feasibility of scaling-up a community-based exercise program for young people with disability. Issue 9 (24th April 2022) - Shields, Nora; Willis, Claire; Imms, Christine; McKenzie, Georgia; van Dorsselaer, Ben; Bruder, Andrea M.; Kennedy, Rachel A.; Bhowon, Yeshna; Southby, Alesha; Prendergast, Luke A.; Watts, Jennifer J.; Taylor, Nicholas F.
Abstract: Purpose: To evaluate feasibility of scaling up a 12-week community-based exercise program ( FitSkills ) in which young people with disability exercise with a student mentor. Method: Within a stepped wedge cluster randomised trial, seven domains of feasibility were assessed: demand, implementation, acceptability, practicality, adaptation, integration, and expansion. Results: Of the 163 participants with disability (61 females; 20.8 ± 5 y) and 226 mentors who enrolled, 123 participants and mentors completed FitSkills . Population demand was estimated at 9% of members of participating organisations. Most participants (76%) completed the twice-weekly program within 12 weeks, attending 79% of sessions (mean 18.9 ± 4.7). Key program elements valued by participants were the mentor, tailored exercise, and regular program schedule. Majority (87%) of mentors were recruited from physiotherapy, occupational therapy, and exercise science courses. Positives for participants were perceived benefits and organisational support, and for mentors, understanding disability. Communication and scheduling were burdens. Three serious and 28 non-serious adverse events occurred. Adaptations (additional screening, risk analysis, extra mentor support, or in-person consultation) enabled 29 young people with complexity to participate. The number of trial sites was expanded to 11 to accommodate participants. Conclusions: Scaling-up FitSkills is feasible, but with caveats related to communication, scheduling, and efficiency of recruitment. IMPLICATIONS FOR REHABILITATION: Key elements valued by participants as part of the successful scale-up of a community-based exercise program ( FitSkills ) across a large metropolitan city included a peer-mentor, tailored exercise, and organisational support structure. FitSkills can be adapted to include young people with complex disability with additional supports including screening, risk analysis, and professional support for the peer-mentor. The benefits of FitSkills, including social connectedness for young people with a disability and normalisation of disability for mentors, outweigh the burdens of participation. Communication with program organisers and scheduling logistics between the young person, their family/carers and peer mentors are important factors to manage for the successful implementation of FitSkills .